Computer assisted learning : CAL into the mainstream : selected contributions from the CAL 93 Symposium : 5-8 April 1993, University of York - Kibby, Michael; Hartley, J. Roger (Pergamon Press, 1994)
This volume contains a selection of the best papers from the Computer Assisted Learning 1993 symposium. The theme of the proceedings, CAL into the mainstream, reflects the growing realization over the past few years that technology has a central role to play in supporting the changes which are taking place in educational provision and practice.